A Data Collection Application for Geosciences Professionals - Carla dos Santos Sá; Danilo Marques de Magalhães (Disegnare con)
This article presents the process of elaborating a web platform that allows the georeferenced data collection in the Twitter API. This platform is intended for people who do not have computer language knowledge, including GIS users, since it simplifies the data collecting method from this social network. Moreover, it enables the realization of up to twelve types of queries that result in georeferenced data. As a case study, queries were made with the ENEM term and spatial analyzes were performed and they are presented in heat maps. The results show that there are no other applications with the same particularities of the present proposal and show possibilities to perform spatial analyzes through the data capture in social networks and GIS processing. DOI: https://doi.org/10.20365/disegnarecon.20.2018.8